SIWEC-R: A rank-sensitive improvement to SIWEC methodology - Trung, Do Duc; Özçalıcı, Mehmet; Ersoy, Nazlı; Duc, Duong Van; Bao, Nguyen Chi; Son, Nguyen Hoai (Universitas Negeri Padang, 2025)
Determining the weights of criteria is a critical step in ranking alternatives characterized by multiple, often conflicting criteria which is a core challenge in Multi-Criteria Decision Making (MCDM). This study introduces the SIWEC-R method, a novel two-stage approach that integrates the SIWEC and R methodology to achieve more accurate and reliable weighting of criteria. Alongside the SIWEC-R method, a new performance metric, the UTAC score, was introduced to capture ranking consistency and strength across various MCDM methods. To ensure a comprehensive evaluation, sensitivity analysis was extended to cover all possible subsets of alternatives, offering an unprecedented level of scrutiny. Comparative assessments across three diverse case studies demonstrated that SIWEC-R consistently outperforms the original SIWEC method, achieving higher Spearman rank correlation coefficients and demonstrating superior robustness under sensitivity analysis. These compelling results firmly establish SIWEC-R as a significant advancement in the field of criteria weighting, delivering enhanced decision-making reliability for complex and uncertain environments.